Sustainability of Demand Responsive Approaches to Rural Water Supply : The Case of Kerala - Andres, Luis; Deb, Saubhik; Gambrill, Martin; Giannone, Elisa; Joseph, George; Kannath, Pramod; Kumar, Manish; Kurian, P.K.; Many, Rajesh; Muwonge, Abdu (World Bank, Washington, DC, 2017)
This paper presents the findings of an impact evaluation to assess the performance and sustainability of the demand responsive community-based approach toward rural water supply in the state of Kerala, India. To achieve the study's objectives, conceptual definitions of the "performance" and "sustainability" of rural water supply schemes were first developed, as were indicators for their systematic measurement. Performance and sustainability indicators for demand responsive approaches were compared with the more conventional supply-based approach to rural water supply. The study found that participatory community driven water supply schemes were more successful in delivering adequate, regular, and quality water supply, experienced fewer breakdowns and water shortages, and enjoyed higher consumer satisfaction with the quality of service delivery. The success of the community-based approach demonstrates that people are willing to contribute toward the capital costs of the schemes and pay for the water they use for a better service delivery. The findings of this paper suggest that the community-based approach can be a superior alternative to traditional supply driven models in expanding and improving water service delivery in rural areas.